P-551 High concordance of the embryonic cell-free DNA with the inner cell mass: impact of blastocyst quality, patient age and mode of fertilization. (30th June 2022) - Navarro Sánchez, L; Ocali, O; García Pascual, C.M; Mamede Andrade, G; Castelló Salom, D; Lai, F; Gross Dutra, C; Rubio, C; Simon, C; Frantz, N; Sakkas, D
Abstract: Study question: Does the embryonic cell-free DNA (cfDNA) in the culture medium represent the chromosomal content of the inner cell mass (ICM)? Which factors impact concordance rates? Summary answer: There is high ploidy concordance between ICM biopsies and embryonic cfDNA. This value is independent of female age, insemination technique and embryo quality. What is known already: The existence of embryonic cfDNA in spent blastocyst medium (SBM) has been confirmed in recent studies, opening a new era of possibilities for non-invasive preimplantation genetic testing for aneuploidy (niPGT-A). High concordance rates of cfDNA with trophectoderm (TE) biopsies and with whole blastocysts have been reported. However, the compartment(s) from where this DNA originates remain unclear. Both TE and ICM are potential sources, but, at the moment, the origin of this cfDNA is unknown as well as the mechanisms underlying its secretion into the medium. Study design, size, duration: We carried out a prospective study to investigate the concordance of cfDNA with the corresponding TE and ICM biopsies. 141 day-6/7 blastocysts were donated for research after written informed consent signature for the project approved by the Ethics Committee. Embryos underwent TE biopsy and SBM collection in the same PGT-A cycle. ICM biopsy in thawed blastocysts was performed after TE biopsy diagnosis. cfDNA, TE and ICM biopsies were analyzed from January 2019 to November 2021. Participants/materials, setting, methods: Embryos were cultured in routine conditions up to day 4. They were then washed and transferred to a new 10μl culture medium droplet. On day 6, SBM was collected and frozen at -20 °C; and blastocyst biopsy and vitrification were performed. Subsequently, blastocysts were thawed and ICM biopsy was conducted. All samples were analyzed by NGS (Ion ReproSeq PGS kit, ThermoFisher Scientific) and the results were analyzed with customized algorithms for TE, ICM and cfDNA. Main results and the role of chance: In combination, the three sample types (cfDNA, ICM and TE) were informative in 81.6% of the blastocysts (115/141). Considering the ICM as the reference, ploidy concordance (i.e. being both euploid or aneuploid) for cfDNA was 86.1% (99/115) and for TE was 89.6% (103/115), without statistical difference. False positive rates were similar for cfDNA and for TE biopsies (6.1% and 9.6%, respectively), and false negative rates were not significantly different, but higher in cfDNA (7.8%) than in TE (0.9%), due to potential contamination with maternal DNA. Ploidy concordance between embryo cfDNA and TE biopsies was 89.6% (103/115). When the results were stratified by female age (≤37 or > 37 years), insemination technique (ICSI or IVF), blastocyst expansion degree (expanded, hatching or fully hatched), and ICM/TE quality (A or B), the informativity of the cfDNA was very similar between the different groups and ranged from 83.7% to 100%. Nevertheless, there were subtle differences for ICM-cfDNA ploidy concordance. It was slightly increased for the older female age group (88.3% vs 83.6% female age ≤37) as well as for ICSI (89.7% vs 82.5% in IVF) and for ICM quality B (88.4% vs 80.0% for ICM A). None of those differences reached statistical significance. Limitations, reasons for caution: When stratifying according to the different criteria, the sample size analyzed was too small to draw strong conclusions. Therefore, more studies, with bigger sample size, are needed to replicate the results. Wider implications of the findings: The embryonic cfDNA released to the culture medium provides information of the overall blastocyst chromosomal constitution, as suggested by the high ploidy concordance rates reported between ICM and cfDNA. This supports the use of niPGT-A as an alternative to other invasive aneuploidy detection methods that require a biopsy. Trial registration number: ClinicalTrials.gov. ID NCT03520933